Expression of Transforming Growth Factor β Type I and II Receptor in Prostate Cancer - Zrage, Hassan H. (Iraqi Journal of Cancer and Medical Genetics, 2017)
This study was carried out to establish the correlation between expression of Transforming growth factor beta receptor one (TGF-βRI) and Transforming growth factor beta receptor two (TGF-βRII) and prostate cancer progression, and to establish the role of prostate cancer development. Immunohistochemistry (IHC) technique was used to detect the level of expression of TGF-βRI and TGF-βRII protein in tissues of patients and healthy control groups. TGF-βR1 protein was expressed in 3 (18.7%) and 14 (56%) of poorly and moderately differentiated malignancy respectively. There was significant difference in mean level of TGF-βRI protein expression among all studied groups. TGF-βRII protein was expressed in 6 (37.5%) and 22 (88%) of poorly and moderately differentiated malignancy respectively, There was significant difference in mean level of TGF-βRII protein expression among all studied groups. We concluded that there was statistically significant association between the loss of expression of TGF-β1 signaling receptors, especially TGF-βRI, and increasing grades of malignancy in prostate cancer, leading to a more malignant phenotype